Differential effects of climate variability on forest dynamics along a precipitation gradient in northern Patagonia - Suarez, Maria Laura (2010)
1. The understanding of the impacts of climate anomalies on demographic processes involvedin forest dynamics is becoming a major global change research objective, as climate-drivendemographic changes have the potential to alter ecological processes and change the compositionof existing communities.2. Here, we test whether the effects of climatic variability on Nothofagus dombeyi forest dynamicsdiffer along the W–E precipitation gradient of northern Patagonia, Argentina, due to differentcontrolling factors along the gradient.3. Using a dendroecological approach, we sampled six N. dombeyi stands along the gradient. Treedeath, growth release and sapling birth dates were obtained and used to reconstruct stand mortality,canopy disturbance and establishment patterns in each stand. Discrete extreme climatic events wereobtained by applying thresholds to meteorological time series. Bivariate event analysis wasperformed to examine the temporal relationships between climate events and forest demographicand canopy disturbance patterns.4. In the xeric region, forest dynamics is driven by drought/heat and humid events. Followingdrought/heat events we observed standing-dead tree mortality, releases in growth, and tree establishmentepisodes. Regional synchrony of these events was coincident with droughts registered fornorthern Patagonia. However, successful establishment was related to wet periods that occurredafter drought events, showing the dependence on favourable periods for growth. For wet regions,demographic patterns showed a temporally uniform pattern but with synchronies at the regionaland local scales. Canopy openings produced by fallen trees, and consequent release in growth andestablishment, were related to both drought and snowy/windy years. The effect of drought in wetregion forests was related mainly to the extreme 1998–99 drought in northern Patagonia.5. Synthesis. Climate in northern Patagonia influences N. dombeyi forest dynamics differentiallyalong a precipitation gradient. In xeric forests, strong but relatively short climatic fluctuationsimpact forest structure through direct effects on tree demography. In wet forests, climatic-inducedmechanical disturbance prevails, driving mortality and subsequent growth and establishment.Considering that recent extreme droughts have the strongest negative impact on N. dombeyipopulations at the eastern distributional limits, a change in distribution of this species as aconsequence of projected climate change is expected.